Talking Local: Florida Consumers' Local Food Purchasing Behaviors - Caroline G. Roper; Joy N. Rumble (EDIS, 2017)
This is a minor revision of an EDIS publication focusing on Florida consumers’ local food purchasing behaviors. It is the second in the Talking Local series, a six-part EDIS publication series about Florida consumers and their perceptions of local food. This series focuses on ways Extension agents can assist Florida farmers and ranchers in the labeling, sale, and promotion of locally-produced products. This series provides information about Florida consumers’ perceptions of local food to Extension faculty who are interested in local food programming or who work with local food clientele. This 5-page publication was written by Caroline G. Roper and Joy N. Rumble, and published by the Department of Agricultural Education and Communication, November 2017.